2(a-4)=2.3d+3

Simple and best practice solution for 2(a-4)=2.3d+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(a-4)=2.3d+3 equation:


Simplifying
2(a + -4) = 2.3d + 3

Reorder the terms:
2(-4 + a) = 2.3d + 3
(-4 * 2 + a * 2) = 2.3d + 3
(-8 + 2a) = 2.3d + 3

Reorder the terms:
-8 + 2a = 3 + 2.3d

Solving
-8 + 2a = 3 + 2.3d

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '8' to each side of the equation.
-8 + 8 + 2a = 3 + 8 + 2.3d

Combine like terms: -8 + 8 = 0
0 + 2a = 3 + 8 + 2.3d
2a = 3 + 8 + 2.3d

Combine like terms: 3 + 8 = 11
2a = 11 + 2.3d

Divide each side by '2'.
a = 5.5 + 1.15d

Simplifying
a = 5.5 + 1.15d

See similar equations:

| 7x+3=8x-13 | | 2x^2-13=17 | | 5x^3+27x^2+10x=0 | | 990000+xy=19999999 | | 14x-20=9x+10 | | 54r^2-24s^2= | | 8=k+5 | | -7y+4y-1=3y+11 | | (xy^3+x)dx+(x^2y^2-y^2)dy=0 | | 5x^3+4x^2-x=0 | | 83-6x=21x+23 | | T=147.94+0.14M | | 3x-27=27 | | 7x+12y=-9 | | 4x+3y=-27 | | n^2=56 | | 3y-4-5y= | | z+3(z-7)=2 | | 4-3x=3x-2-8x | | 1/9=aa+24 | | 2x+y+120=180 | | 5=7-x | | 3(2+w)-4w=3w-10 | | -2=7-x | | 2-(x-3)=4x+15 | | -4=7-x | | -6=7-x | | f(x)=2x^2+3x+6 | | 4=2-4x | | 0=2-4x | | 5x+19=2x+31 | | 8m-2(3m+3)=-5+2m-1 |

Equations solver categories